AI-Driven Fire Detection and Suppression System with Real-Time Remote Monitoring - Metahri Dhiyaeddine; Dekar Amina; SettingsKadi Halima Bouchra (ITEGAM-JETIA)
Fire detection and suppression are essential for the safety of monitored environments. Our project aims to develop an intelligent solution using artificial intelligence AI to optimize these processes. We integrate algorithms to process signals from gas and flame sensors via Arduino and use AI to analyze camera signals to improve accuracy. When a fire detected, a signal sent to an automatic extinguisher for immediate intervention. Additionally, we have designed a remote monitoring platform in Python, enabling real-time system management from a control center. This platform offers proactive management and instant visibility into the status of monitored environments, thereby enhancing overall security. A thorough analysis confirms that our Fire detection System FDS is robust and effective for fire detection and management, ensuring rapid and precise responses, and thus contributing to the safety and peace of mind of users. This system is particularly suited for deployment in high-risk and high-occupancy buildings such as hotels, shopping markets, office complexes, industrial facilities, and residential apartments, ensuring enhanced safety and peace of mind for users